Possible models of local news provision by radio in Scotland: A mixed-methods study. (1st June 2019) - Kocic, Aleksandar; Milicev, Jelena
Scotland does not have any public service radio on a local level, except for a few bulletins or programmes offered by BBC Radio Scotland on an opt-out basis. Scottish commercial radio stations do cover local issues but within brief hourly news bulletins, without any in-depth coverage, while community radio by and large lacks resources for any news coverage of its own. Through a review of the existing literature on the role of media in democracy, and in particular the role of local radio, interviews with stakeholders and experts and history, and focus groups with ordinary people, this study formulates several possible solutions for future local news provision by radio in Scotland.